Competency-Based Education in Africa: Exploring Teachers’ Perceptions, Understanding, and Practices (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
This study explored teachers’ knowledge and integration of competency-based practices in schools. One hundred and fifty in-service secondary school teachers were sampled across three African countries using a survey research design. A combination of both closed and open-ended questions was used to elicit responses from respondents via an online system. Responses from the open-ended questions were analysed using thematic analysis, and data received from the structured questions were analysed using percentage distribution. The theoretical lens through which this study was viewed was the Human capital theory and social constructivism theory. Findings revealed that teachers across the three countries have a positive perception of the usage of competency-based approaches but lack professional training and support, which in turn affects the quality of their teaching and assessment practices in classrooms. The implications and recommendations from this study offer teachers as well as education stakeholders in Africa valuable consideration to move beyond the traditional level of assessment and integrate good proxies of academic skills that support learners’ acquisition of 21stcentury skills such as problem-solving, creativity and critical thinking in assessing learners’ competencies.
Keywords: competencies; competency-based education; competency-based strategies; competency-based assessment; 21st century skills